Konsumsi Tahu Kedelai Hitam untuk Memperbaiki Nilai SGOT/ SGPT dan Aktivitas Antioksidan Plasma Penderita Diabetes Tipe 2 - Fransiska Rungkat Zakaria; Delina Puspa Rosana Firdaus; Nancy Dewi Yuliana (Perum BULOG, 2016)
Type 2 diabetes mellitus pathogenesis is characterized by high blood glucose which can be triggered by several factors such as oxidative stress, unhealthy diet, and poor lifestyle. The high content of bioactive components and low content of digestible carbohydrate in black soybeans tofu might contribute to the body antioxidant supply and control blood glucose levels. This study aimed to evaluate the effects of black soy tofu consumption toward plasma SGOT/SGPT and antioxidant capacity. The intervention of black soybean tofu was conducted for 28 days in 15 type-2 diabetic respondents. The results showed that black soybean tofu significantly (p ˂ 0.05) increased plasma antioxidant activity level of respondents, from 45.79 ± 3.31 percent to 53.05 ± 4.44 percent. SGOT / SGPT tests showed a decrement ((p ≥ 0.05), from 14.27 ± 3.81 / 21.07 ± 6.73 (U/L) to 12.73 ± 2.34 / 18.60 ± 4.29 (U/L). The processing of black soybeans into tofu caused a decrease in antioxidant activity, from 144.06 mg AEAC to 45.27 mg AEAC and the total anthocyanin, from 12.27 mg to 1.805 mg/100 g. The results suggested that black soybean tofu improved the health profile of the diabetic respondents by increasing plasma antioxidant capacity and decreasing plasma SGOT/SGPT level.